Modulation of GSK-3 as a Therapeutic Strategy on Tau Pathologies - Medina, Miguel; Garrido, Juan Jose; Wandosell, Francisco G. (Frontiers in Molecular Neuroscience, 2011)
Glycogen synthase kinase 3 (GSK-3) is ubiquitously expressed and unusually active in resting, non-stimulated cells. In mammals, at least three proteins (,  and generated from two different genes, gsk3 and gsk3 are widely expressed at both the RNA and protein levels although some tissues show preferential expression of some of the three proteins. Control of GSK-3 activity occurs by complex mechanisms that depend on specific signalling pathways, often controlling the inhibition of the kinase activity. GSK-3 appears to integrate different signalling pathways from a wide selection of cellular stimuli. The unique position of GSK-3 in modulating the function of a diverse series of proteins and its association with a wide variety of human disorders has attracted significant attention as a therapeutic target and as a means to understand the molecular bases of brain disorders. Different neurodegenerative diseases including frontotemporal dementia, progressive supranuclear palsy, and Alzheimer’s disease, present prominent tau pathology such as tau hyperphosphorylation and aggregation and are collectively referred as tauopathies. GSK-3 has also been associated to different neuropsychiatric disorders, such as esquizofrenia and bipolar disorder. GSK-3is the major kinase to phosphorylate tau both in vitro and in vivo and has been proposed as a target for therapeutic intervention. The first therapeutic strategy to modulate GSK-3 activity was the direct inhibition of its kinase activity. This review will focus on the signalling pathways involved in the control of GSK-3 activity and its pathological deregulation. We will highlight different alternatives of GSK-3 modulation including the direct pharmacological inhibition as compared to the modulation by upstream regulators.